The Right to Education in AU Law - Garrido, R.; Aua Baldé (The Emergent African Union Law: Conceptualization, Delimitation, and Application, 2021)
Education is considered fundamental for the realization of other rights. Although not expressly mentioned, it underpins the entire African Union Agenda 2063. This chapter analyses and assesses how education is enshrined as a fundamental right in the AU’s legal framework as well as its broader role within the AU legal system, while bearing in mind the relevance of education to achieve the goals set by Agenda 2063. It discusses the right of Africans to education, but also how AU law fosters education as a right, and how the Union is developing policies and a holistic strategy actively to guarantee this right to African citizens. By looking at the role of education in AU law, this chapter aims to shed light on existing gaps and offer a perspective on the way forward for AU law.